Meiotic Studies on Combinations of Chromosomes With Different Sized Centromeres in Maize - Han, Fangpu; Lamb, Jonathan C.; McCaw, Morgan E.; Gao, Zhi; Zhang, Bing; Swyers, Nathan C.; Birchler, James A. (Frontiers in Plant Science, 2018)
Multiple centromere misdivision derivatives of a translocation between the supernumerary B chromosome and the short arm of chromosome 9 (TB-9Sb) permit investigation of how centromeres of different sizes behave in meiosis in opposition or in competition with each other. In the first analysis, heterozygotes were produced between the normal TB-9Sb and derivatives of it that resulted from centromere misdivision that reduced the amounts of centromeric DNA. These heterozygotes could test whether these drastic differences would result in meiotic drive of the larger chromosome in female meiosis. Cytological determinations of the segregation of large and small centromeres among thousands of progeny of four combinations were made. The recovery of the larger centromere was at a few percent higher frequency in two of four combinations. However, examination of phosphorylated histone H2A-Thr133, a characteristic of active centromeres, showed a lack of correlation with the size of the centromeric DNA, suggesting an expansion of the basal protein features of the kinetochore in two of the three cases despite the reduction in the size of the underlying DNA. In the second analysis, plants containing different sizes of the B chromosome centromere were crossed to plants with TB-9Sb with a foldback duplication of 9S (TB-9Sb-Dp9). In the progeny, plants containing large and small versions of the B chromosome centromere were selected by FISH. A meiotic “tug of war” occurred in hybrid combinations by recombination between the normal 9S and the foldback duplication in those cases in which pairing occurred. Such pairing and recombination produce anaphase I bridges but in some cases the large and small centromeres progressed to the same pole. In one combination, new dicentric chromosomes were found in the progeny. Collectively, the results indicate that the size of the underlying DNA of a centromere does not dramatically affect its segregation properties or its ability to progress to the poles in meiosis potentially because the biochemical features of centromeres adjust to the cellular conditions.